Development of Interactive Learning Media Based on Android Using Ispring Suite 9 Power Transfer in Class XI TKR SMK Negeri 1 Percut Sei Tuan - Samuel Marbun; Zainal Arifin (Educational Dynamics: International Journal of Education and Social Sciences, 2025)
This research aims to develop interactive learning media based on android with iSpring Suite 9 which is feasible and effective in the learning process of Chassis Maintenance and Power Transfer. The type of research used is development research (Research & Development) using the ADDIE development model which has 5 stages namely Analysis, Design, Development, Implementation and Evaluation. The results of the research in the feasibility test of interactive learning media based on media validation by media experts obtained a score of 3.70 in the ‘very feasible’ category, learning design experts obtained a score of 3.71 in the ‘very feasible’ category, and material experts obtained a score of 3.96 in the ‘very feasible’ category. The results of the one to one trial of students obtained a score of 3.50 with the category ‘very feasible’, the small-scale trial of students obtained a score of 3.65 with the category ‘very feasible’, and the large-scale trial of students obtained a score of 3.71 with the category ‘very feasible’. The results of the research in the effectiveness test of interactive learning media are known based on the results of the pre-test and post-test there was an increase in value of 41.29, as well as the average N-Gain value of 0.77 in the high category with a percentage of 76.56% in the effective category. So it can be concluded that android-based interactive learning media using Ispring Suite 9 is very feasible to use as a learning media and effective to use because it can improve student learning outcomes in Chassis Maintenance and Power Transfer subjects in class XI TKR SMK Negeri 1 Percut Sei Tuan.